The Morphology of Pollen Grains of the Some Species of Rosaceae Juss. Family - Motyleva, Svetlana; Brindza, Jan; Kulikov, Ivan (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Features of pollen grains, sculpture 2 species Rosaceae Juss. (Malus domestica Borkh and Pyrus communis L.) has been studied in detail using scanning electron microscopy method. The pollen material is picked up in Slovak Republic, was used in the study. Shape of the pollen grains is oblong-ellipsoidal. In terms of poles, the grain is round. The pollen grains Malus domestica and Pyrus communis has – 3 colossus, the hole is long. A complex type of exine is characteristic of the studied species of Rosaceae. The average size of the poles axis of pollen grains is Malus domestica trees is in the range of 27.91–36.62 μm, the equatorial diameter is in the range of 13.28–17.17 μm. The average size of the pole axis of pollen poles of Pyrus communis trees is 38.83–56.83 μm, the equatorial diameter is 20.26–29.92 μm. The ratio of the pole axis to the equatorial (P/E) is the degree of elongation of the pollen grains (roundness).The pollen of Malus domestica breeds is more elongate compared with the pollen of Pyrus communis. Pollen of Malus domestica rocks are more elongated compared with the pollen of Pyrus communis (Р/Е is 14% more). The traits analysed could be useful for plant breeders or for gene bank curators at the first steps of identification of cultivars, since the analysis is simpler and less expensive than other methods.